PREVALENCE OF UNRUPTURED INTRACRANIAL ANEURYSMS IN PATIENTS WITH ABDOMINAL AORTIC ANEURYSMS IN SOUTH-WESTERN FINNISH POPULATION - Mustamäki, Julia (My University, 2025)
Previous studies have suggested high prevalence between abdominal aortic aneurysms (AAA) and intracranial aneurysms (IA). Research in converse study design is highly limited with considerable variability. Aneurysmatic diseases of arteries may affect any arteries and intracranial and abdominal aortic aneurysms are among the most common occurrences. Both have high morbidity and mortality. Studies have shown that they share common risk factors such as tobacco use and high blood pressure. Aim of this study is to establish prevalence of unruptured intracranial aneurysms (UIA) in patients with abdominal aortic aneurysms in South-Western Finnish population. Inclusion criteria included all abdominal aortic aneurysms from suprarenal to proximal iliac arteries. Retrospective analysis of all patients who underwent brain magnetic resonance angiography (MRA) or computed tomography angiography (CTA) between 2005 and 2019 at a single tertiary care center (N=48,037). Patients with available abdominal aortic imaging (CTA or ultrasonography) were included. Radiology reports were reviewed for the presence of UIAs and AAAs. The prevalence of UIAs was significantly higher in patients with AAAs compared with those without AAAs (6.7% vs. 3.9%, P=0.002). The majority of AAA patients were male and AAA patients were older. This encourages developing protocol to recognize patients at risk and for targeted screening. Further research is needed to evaluate the cost-effectiveness and overall impact of such an approach on quality of life and survival.
Keywords: Intracranial aneurysm, Abdominal aortic aneurysm, Arteries, Finland